The Compare Analysis of Guidance and Counseling Services in Indonesian Schools of Kuala Lumpur (SIKL) And Schools In Kudus Indonesia - Putri Eka Damayanti; Khilman Rofi Azmi (Pamomong: Journal of Islamic Educational Counseling, 2021)
This article aims to find out the analysis of guidance and counseling services in Kuala Lumpur Indonesian schools with in Indonesian schools (Kudus). Research method using a qualitative method by using a descriptive approach study that aims to understand in depth the object that is examined. The results showed that One of the counseling guidance services in SIKL uses the support system by directing parents to participate in supervising students in the online learning process. Beside, in SIKL all teachers provide guidance and counseling services while schools in Indonesia are only counseling guidance teachers who provide guidance and counseling services. Counseling tutors in SIKL have an important role in school because counseling teachers are educators who serve and facilitate the development of all potential learners to plan for a good future from various aspects, ranging from personal, psychological, and social. Guidance and counseling services in Indonesian schools in their implementation are made the preparation or planning of counseling guidance programs. The guidance and counseling program in Kudus Indonesian schools has four services, namely: (1) Basic services, (2) Responsive services, (3) Individual planning services, and (4) System support. The conclusion in this study is the selection of appropriate counseling guidance services and a good approach will make it easier for teachers to guide counseling in helping to solve student problems.